2011
DOI: 10.1097/tp.0b013e3182003d76
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Mycophenolate Mofetil Versus Enteric-Coated Mycophenolate Sodium in Primary Renal Transplantation With Tacrolimus and Steroid Avoidance: Four-Year Analysis

Abstract: This is the first long-term, randomized trial comparing enteric-coated mycophenolate sodium versus mycophenolate mofetil along with reduced maintenance tacrolimus dosing and steroid avoidance, which resulted in similarly low-BPAR rates, acceptably high renal function at 48 months, and an equivalent side effect profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
1
25
1
1
Order By: Relevance
“…14 Current literature has debated whether MMF or MPS offers a better side effect profile. 27,28 All patients in this study were initially placed on MMF. One patient was switched to MPS secondary to hypokalemia, myalgia, insomnia, and anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…14 Current literature has debated whether MMF or MPS offers a better side effect profile. 27,28 All patients in this study were initially placed on MMF. One patient was switched to MPS secondary to hypokalemia, myalgia, insomnia, and anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…We were therefore interested in determining the prognostic impact of NODAT among patients receiving transplants at our centre. To maximise statistical power, we combined data for all study participants in four randomised immunosuppression trials of adult, primary kidney transplantation performed at our centre since May 2000 [22][23][24][25][26][27][28][29][30][31][32], yielding a prospectively followed cohort of 628 patients. Results from this observational study are presented here.…”
Section: Introductionmentioning
confidence: 99%
“…: NCT00681213, NCT00685061, NCT00681343, NCT00533624 and NCT01172418; note: two distinct registration numbers exist in the second trial, because separate randomisations of deceased donor and living donor recipients were performed). Results of these randomised trials have been reported previously (details omitted here) [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This may help alleviate some of the gastrointestinal side effects of mycophenolate mofetil. There is no significant difference in rejection and side effects in large randomized trial of mycophenolate mofetil versus mycophenolate sodium (Ciancio et al, 2011). The ability of mycophenolic acid to facilitate sparing of other immunosuppressive agents, particularly cyclosporine and its related nephrotoxicity, is promising.…”
Section: Mycophenolic Acidmentioning
confidence: 92%